Description of two ubiquitous species of Desmosomatidae (Isopoda: Asellota) from the Northwest Pacific Basin east of the Kuril-Kamchatka Trench - Golovan, Olga A. (Zootaxa, 2015)
Two new species of Desmosomatidae, Eugerdella kurabyssalis sp. nov. and Parvochelus serricaudis sp. nov., are described from the Northwest Pacific open abyssal plain to the east of the Kuril-Kamchatka Trench. These species constituted about one fourth of all collected desmosomatid specimens of the KuramBio expedition (2012), indicating it may be the most abundant species of the family in this area. E. kurabyssalis sp. nov. is rather similar to E. minutula Mezhov, 1986 and E. theodori Brix, 2007, resembling them in the shape of its body segments and appendages, including the absence of the mandibular palp and morphology of the pereopod I. The new species can be distinguished from the mentioned species by the number of cusps of the mandibular incisor process and lacinia mobilis, the relatively stouter pereopods and different setation of the pereopod I ischium. P. serricaudis sp. nov. is the second species of the genus Parvochelus Brix & Kihara, 2015 (see Brix et al. 2015) and the first record of the genus from the Pacific Ocean and from the Northern Hemisphere. P. serricaudis sp. nov. can be distinguished from P. russus Brix & Kihara, 2015 by its relatively stouter pereopod I, presence of the mandibular palp and the shape of the maxilliped palp articles and female operculum. A discussion of the taxonomic characters and the modified diagnosis of the genus Parvochelus are presented.